Pediatric Rapid Response Nurse Deployment to Pediatric Trauma Activations: A Process Improvement Initiative. Issue 3 (May 2021) - Moss, Lori N.; Cunningham, Aaron J.; Tobias, Joseph; Hamilton, Nick; Jafri, Mubeen
Abstract : Background: Prolonged emergency department length of stay in trauma patients is associated with increased hospital length of stay and inhospital mortality. This problem is compounded in pediatric patients, as injured children have less physiologic reserve and may exhibit only subtle warning signs before decompensation. Objective: To determine the impact of deploying pediatric rapid response nurses to full trauma activations for patients transferred to the pediatric intensive care unit on emergency department length of stay. Methods: This is a before-and-after analysis of a quality improvement initiative deploying pediatric rapid response nurses to full trauma activations. Trauma registry data collected from January 2016 to August 2020 were statistically analyzed. Demographic and outcome variables were assessed by unpaired t test and χ 2 analysis. Results: A total of 94 patients met inclusion criteria as full activations admitted to the intensive care unit during the study period. The preimplementation group ( n = 60) was 88% ( n = 53) male, with a median age of 6.9 years and a median Injury Severity Score of 21. The postimplementation group ( n = 34) was 62% ( n = 21) male, with a median age of 5.6 years and a median Injury Severity Score of 17. The emergency department length of stay decreased from median (interquartile range) 48.5 (36.0–84.75) min (preimplementation) to 36.5 (27.5–55.5) min (postimplementation; p = .019). Conclusion: Deployment of pediatric rapid response nurses to full trauma activations facilitates the assessment and transfer of pediatric trauma to the intensive care unit and decreases emergency department length of stay.